A Facile Way to Construct Stable and Ionic Conductive Lithium Sulfide Nanoparticles Composed Solid Electrolyte Interphase on Li Metal Anode. (7th October 2020) - Cui, Yongliang; Liu, Sufu; Wang, Donghuang; Wang, Xiuli; Xia, Xinhui; Gu, Changdong; Tu, Jiangping
Abstract: Due to the high theoretical capacity and low reduction potential, metallic lithium is a promising anode material for the next generation of high‐energy‐density batteries. However, the dynamic Li plating/stripping process can easily destroy the unstable solid electrolyte interphase (SEI) and cause dendrite growth. Here, an artificial lithium sulfide nanoparticle composed SEI layer with superior stability and high ionic conductivity is designed by a spray quenching method. The artificial SEI layer on Li surface can effectively minimize the side reactions and suppress Li dendrite growth, and the metal electrode delivers stable cycling for 500 cycles in the symmetrical cell with carbonate electrolyte. Moreover, when this SEI‐modified Li anode is coupled with a LiFePO4 cathode, the full cell shows promoted cycling stability and rate capability. This work provides a broadly applicable and facile strategy to address the intrinsic issues of lithium metal anodes. Abstract : An artificial lithium sulfide nanoparticles (LSNP) composed solid electrolyte interphase (SEI) layer with superior stability and high ionic conductivity is prepared via a facile spray quenching method. This artificial SEI layer on Li surface could effectively minimize the side reactions and suppress Li dendrite growth. Thus, the LSNP layer‐protected anodes showed superior cycling performance both in the symmetrical cells and full cells.